Time-resolved synchrotron tomographic quantification of deformation-induced flow in a semi-solid equiaxed dendritic Al–Cu alloy. (1st July 2015) - Cai, B.; Karagadde, S.; Rowley, D.; Marrow, T.J.; Connolley, T.; Lee, P.D.
Abstract : The rheology of semi-solid alloys has been studied by a novel in situ tomographic technique. Via extruding an equiaxed Al–15 wt.%Cu alloy, the inhomogeneous coherent compression of the α-Al grains was quantified, including the interdendritic channel closure and formation of a liquid extrudate. This investigation not only provides important insights into the microstructural changes occurring during semi-solid deformation, but also offers a validation benchmark for segregation and rheological models.